Intradialytic Cognitive and Exercise Training May Preserve Cognitive Function - Mara A. McAdams-DeMarco; Jonathan Konel; Fatima Warsame; Hao Ying; Marlís González Fernández; Michelle C. Carlson; Derek M. Fine; Lawrence J. Appel; Dorry L. Segev (Kidney International Reports, 2018)
Cognitive decline is common and increases mortality risk in hemodialysis patients. Intradialytic interventions like cognitive training (CT) and exercise training (ET) may preserve cognitive function. Methods: We conducted a pilot randomized controlled trial of 20 hemodialysis patients to study the impact of 3 months of intradialytic CT (tablet-based brain games) (n = 7), ET (foot peddlers) (n = 6), or standard of care (SC) (n = 7) on cognitive function. Global cognitive function was measured by the Modified Mini Mental Status Exam (3MS), psychomotor speed was measured by Trail Making Tests A and B (TMTA and TMTB), and executive function was assessed by subtracting (TMTB − TMTA). Lower 3MS scores and slower TMTA and TMTB times reflected worse cognitive function. P values for differences were generated using analysis of variance, and 95% confidence intervals (CIs) and P values were generated from linear regression. Results: Patients with SC experienced a decrease in psychomotor speed and executive function by 3 months (TMTA: 15 seconds; P = 0.055; TMTB: 47.4 seconds; P = 0.006; TMTB − TMTA; 31.7 seconds; P = 0.052); this decline was not seen among those with CT or ET (all P > 0.05). Compared with SC, the difference in the mean change in 3MS score was −3.29 points (95% CI: −11.70 to 5.12; P = 0.42) for CT and 4.48 points (95% CI: −4.27 to 13.22; P = 0.30) for ET. Compared with SC, the difference in mean change for TMTA was −15.13 seconds (95% CI: −37.64 to 7.39; P = 0.17) for CT and −17.48 seconds (95% CI: −41.18 to 6.22; P = 0.14) for ET, for TMTB, the difference was −46.72 seconds (95% CI: −91.12 to −2.31; P = 0.04) for CT and −56.21 seconds (95% CI: −105.86 to −6.56; P = 0.03) for ET, and for TMTB – TMTA, the difference was −30.88 seconds (95% CI: −76.05 to 14.28; P = 0.16) for CT and −34.93 seconds (95% CI: −85.43 to 15.56; P = 0.16) for ET. Conclusion: Preliminary findings of our pilot study suggested that cognitive decline in psychomotor speed and executive function is possibly prevented by intradialytic CT and ET. These preliminary pilot findings should be replicated.